А SURVEY OF THE FACTORS INFLUENCING INDIVIDUAL INVESTORS’ INVESTMENT DECISION MAKING IN THE MONGALIAN CAPITAL MARKET - Nadmid, Batjargal; Badnaavanchin, Buyannemekhnyam (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study analyzed and evaluated the influence of various factors on individual investment decision-making, including personal, socio-economic, market, financial, and accounting information, as well as company operations and characteristics. The factors affecting individual investments were selected from indicators studied in similar research, with significant overlap, and primary data was collected and processed using research methods. The findings indicate that financial and accounting information plays a predominant role in shaping individual investment decisions.